Measurement of B(Λc+→pK-π+) - Jaffe, D; Masek, G; Paar, H; Potter, E; Prell, S; Sharma, V; Asner, D; Eppich, A; Gronberg, J; Hill, T; Lange, D; Morrison, R; et al. (2000)
The Λc+→pK-π+ yield has been measured in a sample of two-jet continuum events containing both a charm tag ("D̄") as well as an antiproton (e+e-→D̄p̄X), with the antiproton in the hemisphere opposite the D̄ (measurement of charge conjugate modes is implicit throughout). Under the hypothesis that such selection criteria tag e+e-→D̄p̄Λc+X events, the Λc+→pK-π+ branching fraction can be determined by measuring the pK-π+ yield in the same hemisphere as the antiprotons in our D̄p̄X sample. Three types of D charm tags are used, πsoft- (from D*-→D̄0πsoft-), electrons (from D̄→Xe-v), and fully reconstructed D̄0→K+π- or D- →K+π-π- or Ds-→φπ-. Combining our results obtained from the three independent charm tags, we obtain B(Λc+→pK-π +)=(5.0±0.5±1.2)%. ©2000 The American Physical Society.